P276 Cardiovascular safety of extrafine single inhaler triple combination of beclometasone dipropionate, formoterol fumarate, and glycopyrronium bromide in copd: results of safety analysis from the trilogy and trinity studies. (15th November 2017) - Scuri, M; Singh, D; Papi, A; Corradi, M; Montagna, I; Francisco, C; Cohuet, G; Vezzoli, S; Muraro, A; Petruzzelli, S; Vestbo, J
Abstract : Rationale: COPD often co-exists with other chronic diseases that can contribute to patients' health status and prognosis. In particular, patients with COPD are at greater risk of cardiovascular disease compared with age and sex-matched controls. Methods: Two 52 week multi-centre, randomised, double-blind, active-controlled studies recruited patients with symptomatic COPD, severe to very severe airflow limitation, and an exacerbation history. In TRILOGY, patients were randomised (1:1) to an extrafine fixed triple combination of beclometasone dipropionate, formoterol fumarate, and glycopyrronium bromide (BDP/FF/GB; 100/6/12.5 mcg, two actuations twice daily [BID] via pressurised metered dose inhaler [pMDI]; 'fixed triple') or an extrafine fixed combination of BDP/FF (100/6 mcg, two actuations BID via pMDI; Fostair) (Singh et al. Lancet 2016; 388: 963–73). In TRINITY patients were randomised 2:2:1 to BDP/FF/GB, tiotropium (18 mcg once daily via single-dose dry powder inhaler [SDDPI]), or BDP/FF+tiotropium: free triple (Vestbo et al. Lancet 2017; 389: 1919–29). In this analysis, we evaluated the occurrence of Major Adverse Cardiovascular Events (MACEs). MACEs included acute myocardial infarction, stroke, cardiovascular death, arrhythmias, and heart failure. Results: MACE incidence and rate in the two BDP/FF/GB groups was similar to the BDP/FF and tiotropium groups (Table 1). The majority of reported MACEs were severe in intensity, with a slightly higher percentage of fatal events in the Tiotropium only group. Importantly, in patients with relevant concomitant cardiovascular diseases, the trend was similar to that seen in the overall populations. None of the other subgroup analyses (by age, spacer use and gender) highlighted relevant differences in the safety profiles compared with the overall population. Conclusions: These Results provide further reassurance that the additional clinical benefits of this extrafine fixed triple compared to standard treatment are not associated with a greater impact on the cardiovascular safety in severe to very severe COPD patients, further supporting its positive benefit/risk ratio. Importantly, the presence of concomitant cardiac comorbidities did not influence the rate of cardiovascular events. Please refer to page A261 for declarations of interest in relation to abstract P276.